IntegraValor - integrated strategy of valorization of agri-food waste - Gomes, Leonardo Corrêa (2022)
The fruit and wine industries represent important sectors in Portugal, generating different products and allowing numerous jobs. However, at the same time, they also generate different bioresidues as peels, skins, peduncles, and non-compliant fruits that are not properly recovered by the industry (Farina et al., 2019). The accumulation of large amounts of this waste biomass often causes potential environmental impact, along with the loss of material that can be processed to produce a high number of value-added products, such as foodstuffs, biofuels, chemicals, pharmaceuticals, and others molecules of interest